2008
DOI: 10.1051/0004-6361:20079157
|View full text |Cite
|
Sign up to set email alerts
|

Line ratios from shocked cloudlets in planetary nebulae

Abstract: Context. Some PNe and PPNe show compact knots, travelling at high velocities away from the central sources.Aims. We compute a number of models from which we obtain predictions of the emission-line spectrum, which can be compared with the spectra of the observed knots. Methods. We completed a series of 11 axisymmetric simulations of an initially spherical cloudlet, travelling away from a photoionizing source, into a uniform medium. The simulations included a multi-frequency transfer of the ionizing radiation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 21 publications
9
84
0
2
Order By: Relevance
“…ner gap and elongation in the N-S direction closely mirrors the elliptical shape and cross-section of the gap in Model A. We interpret the ionisation structure of the 'ears' or 'multiple-shells' referred to by previous authors as shocked outflows similar to IC 4634 and M 3-16 (Raga et al 2008; Sec. 4.5.1).…”
Section: K 1-2supporting
confidence: 81%
See 3 more Smart Citations
“…ner gap and elongation in the N-S direction closely mirrors the elliptical shape and cross-section of the gap in Model A. We interpret the ionisation structure of the 'ears' or 'multiple-shells' referred to by previous authors as shocked outflows similar to IC 4634 and M 3-16 (Raga et al 2008; Sec. 4.5.1).…”
Section: K 1-2supporting
confidence: 81%
“…These features are well-reproduced by models as fastmoving photo-ionised neutral clumps (Raga et al 2008). The [NII] image of M 3-16 also reveals low-ionisation filaments and some knots which do not display the same high degree of point symmetry as in IC 4634.…”
Section: -16mentioning
confidence: 55%
See 2 more Smart Citations
“…These diagrams also give information on the excitation mechanism (photoionization, shock excitation or mixed). In this figure we have adapted these diagrams including the most recent compilation of HH objects (Raga et al 1996), a sample of proto-PNe (Raga et al 2008) and the irradiated shock models from the work of Raga et al (2008). The PN region is adopted from Riesgo & López (2006 Raga et al 1996) are shown as black dots.…”
Section: Intrinsic Emission: Emission Line Ratios and Nebular Diagnosmentioning
confidence: 99%